A New Metaheuristic Inflation Data for Real & Reactive Power Generator Restraints - Parthiban, S.; Karthikeyan, P.; Poongodi, P.; Balamurugan, P. (International Journal of Psychosocial Rehabilitation, 2019)
To enhance the real and reactive power of the generator vary with in the certain limit and fulfills the load demand with less fuel cost, such as power balance. A divergent of the basic PSO method, is determined by incorporating chaotic sequences to enhance its consummanation. Two different example problems comprising 6 and 15 generating units are solved to demonstrate the effectiveness of the specific task. The results of CPSO are compared with GA and PSO techniques. The generation costs is lower, New method can result in great economic effect. For ELD problems, the CPSO method is more feasible and effective alternative approaches than the traditional particle swarm optimization algorithm